A percepção pública da ciência e a formação da cultura científica no âmbito escolar - Benassi, Cassiane Beatrís Pasuck (2016)
Science is part of the culture built by the society over the years, and is a way of observing the world, to understand, to criticize and value. It can be said that one of the purposes of teaching Science in schools is the cultural transmission of knowledge, based on the prior knowledge, being it from a common sense, religious or mythical by the student to scientific knowledge. It must be considered the role of communication in the construction and evaluation of knowledge, considering the language as one of the main aspects for Science, for Education and for the Science Education. Starting from this context, the aim of this research was do an analysis with students of the third year of high school in five schools of the network State education of Cascavel, PR, Brazil, on the extent of interest, information and knowledge of science and the effects on their attitudes towards the society. The work involved, beyond the field research, literature review in articles, scientific journals, theses and indicators of public perception of national and international Science and a comparative with researches in the school environment. Questionnaires were applied to 261 students and interviews were made with a sample of these, in order to seek evidence of how is happening the formation of scientific culture in the school environment and the reflections caused by the production of knowledge looking beyond the school walls. In the data analysis were established categories based on content analysis according to Bardin (2011) through some convergences and divergences of opinion about Science, religion and scientific knowledge of students. With that information, it was possible to observe that the interviewed students have a naive and stereotypical view of the scientist and the experimental activity, they also have an empiricist view of science. The students show interest for science and technology, but do not associate the responses to everyday life. They highlight the needs of an significant education in school, a greater investment in education and in teacher training, generating behaviors contextualized from these professionals in Science classes.